Breast cancer survivors. Early diagnosis – successful treatment – quality of life: multidisciplinary approach - Tatarchuk, T. F.; Smolanka, I. I.; Popkov, O. V. (REPRODUCTIVE ENDOCRINOLOGY, 2016)
Breast cancer is the leading cause of cancer-related deaths in European women. Breast cancer diagnosis is widely represented in women with such risk factors as exposure of endogenous end exogenous estrogens, some genetic predispositions, low parity and others. Consumption of fat, alcohol leads to the rising breast cancer incidence of last decades. Breast cancer occurs mostly after 50 years. Genetic BRCA1 and BRCA2 polymorphism, family history allows supposing breast cancer in 10% of women in risk group. In Ukraine radiation played a great role due to Chernobyl atomic station catastrophe in 1986. In a treatment of breast cancer different methods are used in a combination. Primary surgery and systemic approaches include radiation therapy, hormone therapy and chemotherapy. Important role belongs to a chemotherapy and post-treatment after surgical intervention. Chemotherapy is recommended in the vast majority of triple-negative, HER2-positive breast cancer and in high-risk luminal HER2-negative tumors (evidence level I, A). The absolute benefit from chemotherapy is more pronounced in estrogen receptors negative tumors. The most frequently used regimens contain anthracyclines and/or taxanes, although in selected patients the CMF therapy (cyclophosphamide, methotrexate, and fluorouracil) may still be used. Endocrine therapy is indicated in all patients with detectable estrogen receptors expression irrespective of the use of chemotherapy and/or targeted therapy (evidence level I, A). Routine physical examinations with a careful taking history are the most valuable measures of detecting breast cancer recurrence. The European Society for Medical Oncology recommends regular visits every 3 to 4 month in the first 2 years, every 6 month from years 3 to 5 and annually thereafter.